Making small animals big - The Tadpoles of Borneo Project - Haas, Alexander; Das, Indraneil (World Congress of Herpetology, 2023)
The article describes the Volkswagen Stiftung funded tadpoles of Borneo project, executed by Alexander Haas and Indraneil Das.